The Dielcometric Method of Measurement of Soil Moisture (TDR method) - Аsgarov, К.А.; Маrdаkhаyеv, А.V.; Khidirov, А.Sh. (Herald of Azerbaijan Engineering Academy, 2022)
Taking into account the fact that the TDR (Time Domain Reflectometry) - method is based on the technique of fault detection in cable lines, the article briefly describes the methodology of fault location in them, specifies the composition of the equipment, considers classical variants of TDR probe designs, gives the equations recommended for conducting the geometric coefficient analysis of probes, gives recommendations for probe design and their application. The calibration equations obtained by G. Topp in coauthorship and Maxwell De Loor for calculations for determination of soil moisture content are presented and recommendations for application of these equations are given. We consider it necessary to note that the recommendations stated in the article will serve as an informative guide to the technical aspects in conducting measurements of soil dielectric permittivity and volumetric water content using TDR equipment both for novice researchers and for experts.